ISOLATION AND CHARACTERIZATION OF PHOSPHATE SOLUBLIZING BACTERIA FROM ANAND AGRICULTURE SOIL. : Life Science-Botany - SAGERVANSHI, AMIT; KUMARI, PRIYANKA; NAGEE, ANJU; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
Phosphorus is vital to seed formation and its content is higher in seeds than in any other part of the plant. It helps plants to survive winter rigors and also contributes to disease resistance in some plants. Also known to improve quality of many fruits, vegetables and grain crops.The inoculation of P-solubilizing microorganisms is a promising technique because it can increase P availability in soils fertilized with rock phosphates. In the present work we have made efforts to isolate the phosphate solubilizing microorganism form soil followed by its biochemical and molecular characterization